Optical and electronic properties of transparent conducting Ta:TiO2 thin and ultra-thin films: the effect of doping and thickness. Issue 21 (28th September 2021) - Bricchi, Beatrice R.; Sygletou, Maria; Ornago, Luca; Terraneo, Giancarlo; Bisio, Francesco; Mancarella, Cristina; Stasi, Lorenzo; Rusconi, Francesco; Mogni, Erika; Ghidelli, Matteo; Biagioni, Paolo; Li Bassi, Andrea
Abstract : The evolution of optical and electronic properties of Ta-doped TiO2  films is investigated as thickness is decreased to 5 nm and as a function of Ta doping. The correlation with structural properties is discussed, showing a high degree of tunability. Abstract : The development of low-dimensional transparent conducting systems is nowadays gaining interest in view of novel optoelectronic applications. In this paper, we investigate the evolution of optical and electronic properties of Ta-doped TiO2 films when their thickness is decreased down to 5 nm and as a function of Ta doping (5–10 at%), and we correlate the observed behavior with the structural properties, showing a high degree of tunability. Ta:TiO2 polycrystalline anatase films are synthetized via pulsed laser deposition, followed by vacuum annealing. For films of thickness 50–200 nm, the electrical resistivity is ∼8 × 10 −4 –1 × 10 −3 Ω cm and the charge carrier density increases with the doping content while the mobility decreases. Below a thickness of 20 nm, the electrical properties partially deteriorate, but still conductive ultra-thin films can be obtained down to 5 nm. The optical response changes with Ta addition, i.e. the absorption band in the UV range blue-shifts, according to the Moss–Burstein effect, while absorption in the IR range increases because of free carriers. Finally, we provide estimates of the effective mass and the plasma energy in the IR range. The fine tunability of the optoelectrical properties of Ta:TiO2 films makes them suitable as transparent conductive components for devices and for photonic or plasmonic applications in the visible and IR ranges.